Simplify.
(-4·3·2)2

Question

Asked 4/27/2015 10:43:36 AM

Updated 6/6/2015 11:49:44 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 11:49:44 AM]

s

= (-24)^2

= 576

= (-7p)(-7p)(-7p)

= (49p^2)(-7p)

= -343p^3

Question

Asked 4/27/2015 10:43:36 AM

Updated 6/6/2015 11:49:44 AM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [6/6/2015 11:49:44 AM]

Rating

3

The expression (2x^2)^3 is equivalent to 8x^6.

Added 4/27/2015 9:25:19 PM

This answer has been confirmed as correct and helpful.

Confirmed by sujaysen [6/6/2015 2:33:13 PM]

Simplify (x 2 y) 3.

Question

Not Answered

Updated 4/27/2015 6:36:31 PM

1 Answer/Comment

(x^2y)^3

= x^6y^3

= x^6y^3

Added 4/27/2015 6:36:31 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [4/27/2015 6:49:41 PM]

Evaluate (x + y )^0 for x = –3 and y = 5. User: Simplify.
n^6 • n^5 ÷ n^4 • n^3 ÷ n^2 • n

Question

Updated 4/27/2015 12:02:13 PM

2 Answers/Comments

(x + y )^0 for x = –3 and y = 5;

(-3 + 5)^0

= 2^0

= 1

(-3 + 5)^0

= 2^0

= 1

Added 4/27/2015 12:02:02 PM

This answer has been confirmed as correct and helpful.

n^6 • n^5 ÷ n^4 • n^3 ÷ n^2 • n

= n^11 ÷ n^4 • n^3 ÷ n^2 • n

= n^7 • n^3 ÷ n^2 • n

= n^10 ÷ n^2 • n

= n^8 • n

= n^9

= n^11 ÷ n^4 • n^3 ÷ n^2 • n

= n^7 • n^3 ÷ n^2 • n

= n^10 ÷ n^2 • n

= n^8 • n

= n^9

Added 4/27/2015 12:02:13 PM

This answer has been confirmed as correct and helpful.

Find the product.
5x^2 · 2y^2

Question

Updated 4/28/2015 3:09:20 AM

1 Answer/Comment

x^5*x^4*x^3

=x^9*x^3

=x^12

=x^9*x^3

=x^12

Added 4/27/2015 8:06:54 PM

This answer has been confirmed as correct and helpful.

Confirmed by yumdrea [4/27/2015 8:14:20 PM]

Find the quotient.
(4ab - 8a^2 + 12ac) ÷ (4a) **Weegy:** (4ab - 8a 2 + 12ac)/(4a) = [(4a)(b - 2a + 3c)]/(4a) = -2a + b + 3c **User:** Find the sum and choose the correct answer.
2n^3 + 4n^2 - 7 and -n^3 - 8n - 2
-n 3 + 4n 2 - 8n - 9
n 3 + 4n 2 - 8n - 9
n 3 + 4n 2 - 8n - 5
n 3 - 4n 2 -9 **User:** How many terms are in the polynomial abcd + e - h^2?
two
three
five
six **Weegy:** There are THREE terms in the polynomial abcd + e - h^2. **User:** Find the product.
y^5 · y^3 **User:** Write xyyzzz in exponential form. (More)

Question

Not Answered

Updated 4/28/2015 3:11:51 AM

3 Answers/Comments

2n^3+4n^2-7+(-n^3-8n-2)

=2n^3-n^3+4n^2-8n-7-2

=n^3+4n^2-8n-9

=2n^3-n^3+4n^2-8n-7-2

=n^3+4n^2-8n-9

Added 4/27/2015 8:16:15 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [4/28/2015 3:12:33 AM]

y^5*y^3

=y^8

=y^8

Added 4/27/2015 8:16:40 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [4/28/2015 3:12:35 AM]

xyyzzz

=xy^2z^3

=xy^2z^3

Added 4/27/2015 8:17:10 PM

This answer has been confirmed as correct and helpful.

Confirmed by Andrew. [4/28/2015 3:12:38 AM]

Find the product.
8y 3(-3y 2) **Weegy:** 8y^3(-3y^2) = -24y^5 **User:** Find the product.
-7(-a 2)(-b 3) **Weegy:** -7(-a^2)(-b^3) = -7a^2b^3 **User:** (k^3)^5 **User:** Find the product.
(10^2)^3 **Weegy:** (10^2)^3 = 10^6 = 1,000,000 **User:** Simplify.
(fg)9 (More)

Question

Not Answered

Updated 6/6/2015 11:52:24 AM

2 Answers/Comments

31,989,235

questions answered

There are no comments.